Comparison of a plant based natural surfactant with SDS for washing of As(V) from Fe rich soil - Mukhopadhyay, S.; Hashim, Mohd Ali; Sahu, J.N.; Yusoff, Ismail; Sen Gupta, B. (Elsevier, 2013)
BACKGROUND: This study explores the possible application of a biodegradable plant based surfactant, obtained from Sapindus mukorossi, for washing low levels of arsenic (As) from an iron (Fe) rich soil. Natural association of As(V) with Fe(III) makes the process difficult. Soapnut solution was compared to anionic surfactant sodium dodecyl sulfate (SDS) in down-flow and a newly introduced suction mode for soil column washing. RESULTS: It was observed that soapnut attained up to 86% efficiency with respect to SDS in removing As. Full factorial design of experiment revealed a very good fit of data. The suction mode generated up to 83 kPa pressure inside column whilst down-flow mode generated a much higher pressure of 214 kPa, thus making the suction mode more efficient. Micellar solubilisation was found to be responsible for As desorption from the soil and it followed 1st order kinetics. Desorption rate coefficient of suction mode was found to be in the range of 0.005 to 0.01, much higher than down-flow mode values. Analysis of the FT-IR data suggested that the soapnut solution did not interact chemically with As, offering an option for reusing the surfactant. CONCLUSION: Soapnut can be considered as a soil washing agent for removing As even from soil with high Fe content.